2013
DOI: 10.3109/17435390.2013.812258
|View full text |Cite
|
Sign up to set email alerts
|

In vitrotoxicity assessment of silver nanoparticles in the presence of phenolic compounds – preventive agents against the harmful effect?

Abstract: The increasing commercial use of silver nanoparticles (Ag-NPs) will inevitably lead to elevated silver exposure and thus to potential human health complications. In this study the acute toxicity of Ag-NPs <20 nm alone and upon co-administration with food matrix component phenolic compounds (PCs) on the cell-based models of the gastrointestinal tract was investigated. An improved co-culture model of Caco-2 and RajiB cells was applied for more precise in vitro simulation of the gastrointestinal tract. The involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 56 publications
4
43
0
Order By: Relevance
“…Again, AgCitrate-NPs exhibited a much weaker effect on tight junction formation in PBCEC. The obtained results of tight junction expression and distribution support the TEER and permeability measurements and are in accordance with the studies of Trickler et al [13] and Martirosyan et al [23]. In addition, the immunofluorescence staining of occludin in the cells of the choroid plexus reveals undisturbed tight junctions, which supports the results of our TEER and permeability measurements.…”
Section: Inflammatory Reaction In Pbcecsupporting
confidence: 93%
See 2 more Smart Citations
“…Again, AgCitrate-NPs exhibited a much weaker effect on tight junction formation in PBCEC. The obtained results of tight junction expression and distribution support the TEER and permeability measurements and are in accordance with the studies of Trickler et al [13] and Martirosyan et al [23]. In addition, the immunofluorescence staining of occludin in the cells of the choroid plexus reveals undisturbed tight junctions, which supports the results of our TEER and permeability measurements.…”
Section: Inflammatory Reaction In Pbcecsupporting
confidence: 93%
“…Within our study we have analyzed the TEER development, permeability against FITC-Dextrane as well as tight junction expression and distribution upon exposure of barrier-forming cells of CNS origin to Ag-NPs. Similarly to the studies of Trickler et al [13] and Martyrosian et al [23] we detected an increase of BBB permeability against FITC-Dextrane after exposure of PBCEC to Ag-NP which has also been confirmed by a decrease of the TER. Again, AgEO-NPs were found to induce a more severe permeability than AgCitrate-NPs.…”
Section: Inflammatory Reaction In Pbcecsupporting
confidence: 89%
See 1 more Smart Citation
“…Cellular uptake has been described, which was suggested to occur through endocytosis (Gaiser et al, 2012). Cytotoxicity data is contradictory, varying from absence of cytotoxicity (Chalew & Schwab, 2013;Bouwmeester et al, 2011), to time and dose dependent cytotoxicity (Bohmert et al, 2012(Bohmert et al, , 2015Martirosyan et al, 2014). The human breast cancer MCF-7 epithelial cell line has been used to create a reference collection of gene-expression profiles following treatment with bioactive small molecules.…”
Section: Introductionmentioning
confidence: 99%
“…14,16,17,29,30 Treatment of proliferating cells with Ag NP for 24 hours decreased the GSH/GSSG ratio to less than half the level in untreated cells, indicating oxidative stress (Figure 8). Other studies in Caco-2 cells have shown induction of oxidative stress by detection of ROS species production 17,31 and gene expression studies showed upregulation of genes involved in oxidative stress in the Caco-2/M cell model. 32 However, some studies have not detected ROS formation in Caco-2 cells.…”
Section: Proliferating Cellsmentioning
confidence: 95%